Hypoxia-inducible lipid droplet-associated induces DGAT1 and promotes lipid storage in hepatocytes - Montserrat A. de la Rosa Rodriguez; Lei Deng; Anne Gemmink; Michel van Weeghel; Marie Louise Aoun; Christina Warnecke; Rajat Singh; Jan Willem Borst; Sander Kersten (Elsevier, 2021)
Objective: Storage of triglycerides in lipid droplets is governed by a set of lipid droplet-associated proteins. One of these lipid droplet-associated proteins, hypoxia-inducible lipid droplet-associated (HILPDA), was found to impair lipid droplet breakdown in macrophages and cancer cells by inhibiting adipose triglyceride lipase. Here, we aimed to better characterize the role and mechanism of action of HILPDA in hepatocytes. Methods: We performed studies in HILPDA-deficient and HILPDA-overexpressing liver cells, liver slices, and mice. The functional role and physical interactions of HILPDA were investigated using a variety of biochemical and microscopic techniques, including real-time fluorescence live-cell imaging and Förster resonance energy transfer-fluorescence lifetime imaging microscopy (FRET-FLIM). Results: Levels of HILPDA were markedly induced by fatty acids in several hepatoma cell lines. Hepatocyte-specific deficiency of HILPDA in mice modestly but significantly reduced hepatic triglycerides in mice with non-alcoholic steatohepatitis. Similarly, deficiency of HILPDA in mouse liver slices and primary hepatocytes reduced lipid storage and accumulation of fluorescently-labeled fatty acids in lipid droplets, respectively, which was independent of adipose triglyceride lipase. Fluorescence microscopy showed that HILPDA partly colocalizes with lipid droplets and with the endoplasmic reticulum, is especially abundant in perinuclear areas, and mainly associates with newly added fatty acids. Real-time fluorescence live-cell imaging further revealed that HILPDA preferentially localizes to lipid droplets that are being remodeled. Overexpression of HILPDA in liver cells increased the activity of diacylglycerol acyltransferases (DGAT) and DGAT1 protein levels, concurrent with increased lipid storage. Confocal microscopy coupled to FRET-FLIM analysis demonstrated that HILPDA physically interacts with DGAT1 in living liver cells. The stimulatory effect of HILPDA on lipid storage via DGAT1 was corroborated in adipocytes. Conclusions: Our data indicate that HILPDA physically interacts with DGAT1 and increases DGAT activity. Our findings suggest a novel regulatory mechanism by which fatty acids promote triglyceride synthesis and storage.